The Effect of CSR, Profitability, and Audit Lag on Going Concern Audit Opinion with Company Size as a Moderating Variable - Wydianti, Lilyana; Aisyaturrahmi (Ebiz Prima Nusa, 2025)
Study This aiming For prove in a way empirical The Influence of Corporate Social Responsibility, Profitability, and Audit Lag on Going Concern Audit Opinion With Company Size as a Moderating Variable. Population in study This is Mining Sector companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023 . The technique of taking sample used​ in study is purposive sampling method through judge sampling and obtained 60 observation data. Data analysis method used in the study This is logistic regression analysis with MRA (Moderated Regression Analysis) approach using STATA 17 application program assistance . Research results This show that (1) Corporate Social Responsibility has an influence positive to going concern audit opinion , (2) Profitability is not influential to going concern audit opinion , (3) Audit Lag has an effect positive to going concern audit opinion , (4) Company Size does not capable to moderate the influence of CSR on going concern audit opinion , (5) Company Size capable moderation The influence of profitability on going concern audit opinion , (6) Company Size does not capable to moderate the influence of Audit Lag on going concern audit opinion